Blindhelper app: aplicativo móvel para acesso por pessoas com deficiência visual a sistemas multimídia com mecanismos de realidade aumentada - Santos, Silas Yudi Konno de Oliveira (2019)
The multimedia systems are mostly composed of visual elements, such as videos, images, graphics, texts and animations. Among multimedia systems, there are advanced visualization systems, whose user interface, for interaction, system manipulation and receiving information, predominantly uses components and visual resources computationally generated. With this, people with visual impairment (PVI) are harmed by being blocked or hindered from interacting with these systems. The “Obras 4D” (“4D Public Works”) is an interactive system for data visualization on public works, under the jurisdiction of the Tribunal de Contas do Estado da Paraíba (“Court of Auditors of the State of Paraíba”). Its objective is to facilitate access to information on works, using their geographical locations as initial access and providing the visualization of their information through augmented reality (AR) mechanisms. In this context, we propose the BlindHelper App, a mobile application capable of giving the PDVs access to the information contained in the “4D Public Works” using technologies present on their mobile devices. As a result of this work, the application BlindHelper App was built with the interaction of the system based on the movements of the hand, captured by the accelerometer contained in the mobile device, and receiving information through audio description of the multimedia elements contained in the original application.